2018
DOI: 10.1002/admt.201800435
|View full text |Cite
|
Sign up to set email alerts
|

Printable Liquid‐Metal@PDMS Stretchable Heater with High Stretchability and Dynamic Stability for Wearable Thermotherapy

Abstract: As a type of flexible electronics, wearable heaters have attracted broad attention because of their giant potential market value, such as for use in wearable thermotherapy. Wearable heaters are required to simultaneously possess high stretchability and dynamic stability, in order to realize joints or muscles thermotherapy during exercising. Here, a high‐performance electrically driven heater using the conductive composite of liquid‐metal (LM) and polydimethylsiloxane (PDMS) is reported, which is patterned as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 44 publications
0
81
0
Order By: Relevance
“…In addition to the sensing and powering capability, the wearable electronics can also perform therapeutic effect. Wang et al reported a wearable electrically driven heater made of conductive composite of LM and PDMS, with sinusoidal patterned structure by direct ink writing technique. The wearable and stretchable heater possesses high stretchability (>100% strain) and excellent conductivity (1.81 × 10 3 S cm −1 ), making it easily be worn on the knee joint and heating during the strenuous exercise.…”
Section: Applications Of Liquid Metal–based Microfluidic Systemsmentioning
confidence: 99%
“…In addition to the sensing and powering capability, the wearable electronics can also perform therapeutic effect. Wang et al reported a wearable electrically driven heater made of conductive composite of LM and PDMS, with sinusoidal patterned structure by direct ink writing technique. The wearable and stretchable heater possesses high stretchability (>100% strain) and excellent conductivity (1.81 × 10 3 S cm −1 ), making it easily be worn on the knee joint and heating during the strenuous exercise.…”
Section: Applications Of Liquid Metal–based Microfluidic Systemsmentioning
confidence: 99%
“…The detailed property and synthesis of this elastic conductor were previously reported by our team. [ 33,34 ] Before the heat curing of electrode material, its rheological and viscosity properties should meet the requirements of conductive inks for printing technology (Figure S3, Supporting Information). This elastic composite conductor exhibits excellent dynamic stability.…”
Section: Resultsmentioning
confidence: 99%
“…First, uncured LMs@PDMS conductor ink (LMs/PDMS = 15:1 by mass) was brushed directly onto the PET mask film, which was pasted on the glass plate. The LMs@PDMS was prepared in the same way as previously reported [33,34 . ] Then, the PET film was peeled off, and LMs@PDMS ink was cured at 80 °C for 2 h to obtain LMs@PDMS electrode with a specific shape (a ring‐shaped top electrode and a disk‐shaped bottom electrode).…”
Section: Methodsmentioning
confidence: 99%
“…And benefited from its melting point, such alloy can also realize convenient phase transition between solid and liquid at the range of room temperature. This is rather desired in many application fields such as flexible electronics, [ 1–3 ] additive manufacturing, [ 4,5 ] wearable devices, [ 6–8 ] biomedical practices, [ 9,10 ] exoskeleton systems, [ 11–13 ] and soft robotics. [ 14,15 ] However, the pretty large density of such metals (usually larger than 5 g cm −3 ) [ 16 ] turns out to be a major concern compared with those non‐metal materials like polymer, plastics, and wood, etc.…”
Section: Introductionmentioning
confidence: 99%